Developing gamified HTML5-based interactive media to improve learning motivation among pre-service elementary teachers (IAIN Kendari, 2026)
Learning that relies heavily on static media often fails to accommodate the characteristics of students as digital natives, resulting in low persistence, interest, and focus during learning. This study aimed to develop HTML5-based interactive media integrated with gamification to enhance the learning motivation of Primary School Teacher Education (PGSD) students at Universitas Negeri Makassar. This study employed a Research and Development (R&D) design using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires, interviews, and documentation. The validation results showed that the developed media was categorized as highly valid by material experts (92.72%) and media/design experts (93.33%). The practicality of the media was also categorized as excellent, as indicated by the results of the one-to-one trial involving seven students (93%) and the small-group trial involving 16 students (90%). Furthermore, the effectiveness test involving 18 students, analyzed using a paired-samples t-test, showed a significant increase in students’ learning motivation (p < .05), with a very large effect size (Cohen’s dz = 3.63) , particularly in the indicators of persistence, interest, and focus after using the media. In conclusion, the gamified HTML5-based interactive media was valid, practical, and empirically shown to improve students’ learning motivation after implementation. Keywords: ADDIE model; gamification; HTML5-based interactive media; learning motivation; Primary School Teacher Education